Analisis Kebijakan Ekonomi Islam Umar Bin Khattab dalam Menghadapi Krisis Telaah Histori dan Implementasi di Era Modern - Annisa Nur’aini; Adinda Farhania Ma’rufa; Seli Saelurrohmah Syam; Lina Marlina (STIKes Ibnu Sina Ajibarang, 2025)
Umar bin Khattab's Islamic economic policy in facing the crisis based on historical review and its relevance in the modern era. As the second Caliph, Umar bin Khattab implemented economic policies based on sharia principles, such as the establishment of Baitul Mal, management of zakat, kharaj, jizyah, and ushr, and the establishment of hisbah institutions to supervise the market. This policy succeeded in creating economic stability through fair distribution of wealth and a subsidy system for the poor. In addition, Umar carried out administrative reforms by establishing a transparent fiscal system and procuring currency to support the country's economy. In the modern context, Umar's economic principles are relevant to addressing global challenges such as social inequality, poverty, and economic crisis. This study confirms that Umar bin Khattab's Islamic economic thinking can be an alternative model that is humanistic and sustainable for current economic development.